THE ANALYSIS OF THE QUALITY OF NATIONAL STANDARDIZED SCHOOL SUMMATIVE EXAMINATION OF ENGLISH SUBJECT 2019 - Nilam Ayuning Herdianti; Rajji K. Adireja; Asep Suparman (Institut Pendidikan Indonesia Garut, 2021)
The national standardized school summative examination (USBN) is the test for measuring student competency achievement, it is constructed by Ministry of Education and Culture (Kemendikbud) about 25% and MGMP Province 75%. However, in improving the quality of the test, it is addition the cognitive dimention of High Order Thinking Skills (HOTS) as the standard. The purpose of this study is to prove the quality of the test in terms of item analysis, distribution of hots and consistency of the test. This study was conducted by analyzing the national standardized school summative examination (USBN) 2019 items, answer sheet, key answer and syllabus.The data was collected from archieves in one of Senior High School. The result shows that the item analysis of the test is valid and reliable, the level of difficulty is not balanced, the discriminating power is sufficient, and the effectiveness of distractor is mostly need revision. Moreover, the distribution of hots has pass the limit and the test consistency is satisfactory in criteria of a good test